Grignard Reagent‐Mediated Regioselective 1,8‐Addition of α‐(2‐Thienylidene)‐β‐ketosulfones - Chang, Meng‐Yang; Chen, Kuan‐Ting; Chen, Hsing‐Yin (Advanced synthesis & catalysis, 2023)
Grignard reagent‐mediated and solvent‐controlled regioselective 1,8‐addition of α‐(2‐thienylidene)‐β‐ketosulfones provides diversified substituted 2‐thienylmethyl β‐ketosulfones in moderate yields in a diethyl ether–dioxane cosolvent and dioxane (v/v=4/1) under ice‐bath conditions. The 1,4‐addition of α‐heterocyclic β‐ketosulfones was also studied. The structure of the key product was confirmed via X‐ray analysis. The uses of various reaction solvents and organomagnesium bromides were investigated for transition metal‐free C−H functionalization. Related plausible mechanisms are proposed and discussed. The DFT calculations are utilized to rationalize the regioselectivity of the 1,8‐addition reaction.